2021
DOI: 10.1002/psc.3325
|View full text |Cite
|
Sign up to set email alerts
|

The ring size of monocyclic ET‐1 controls selectivity and signaling efficiency at both endothelin receptor subtypes

Abstract: Cardiovascular diseases (CVDs) like hypertension are a major cause for death worldwide. In the cardiovascular tissue, the endothelin system—consisting of the receptor subtypes A (ETAR) and B (ETBR) and the mixed agonist endothelin 1 (ET‐1)—is a major key player in the regulation of vascular tone and blood pressure. Tight control of this system is required to maintain homeostasis; otherwise, the endothelin system can cause severe CVDs like pulmonary artery hypertension. The high sequence homology between both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…This sequence difference elicits a hypothesis that ET B R has a larger pocket space to accommodate the bulkier N-terminal region of ET-3, which is supported by a smaller pocket size (1976 Å 3 , calculated by POVME 31 ) for ET A R relative to ET B R (2059 Å 3 ). This conclusion is in agreement with a previous finding that increasing intramolecular ring size decreased peptide activity at ET A R and shifted the peptide towards ET B R selectivity 32 .…”
Section: Resultssupporting
confidence: 94%
“…This sequence difference elicits a hypothesis that ET B R has a larger pocket space to accommodate the bulkier N-terminal region of ET-3, which is supported by a smaller pocket size (1976 Å 3 , calculated by POVME 31 ) for ET A R relative to ET B R (2059 Å 3 ). This conclusion is in agreement with a previous finding that increasing intramolecular ring size decreased peptide activity at ET A R and shifted the peptide towards ET B R selectivity 32 .…”
Section: Resultssupporting
confidence: 94%
“…For activation of the ET B R the recently described monocyclic ET-1 analog [4Ala 1,3,11,15 , Nle 7 ]-ET-1 was used due to its missing ET A R activation properties. [69] As we demonstrated the reduction of ET B R signaling also for ET A R occupied by the competitive antagonist sitaxentan, ligand scavenging by ET A R can be excluded as reason for the reduced ET B R activation. Further studies demonstrated that ET A R expression does not alter the signaling profile of other G q -coupled GPCRs as demonstrated for the AT 1 R. Therefore, it is likely that ET A R selectively impairs ET B R signaling due to close proximity in the cell membrane e. g. by masking intracellular interaction interfaces and, thus, delaying the initial effector coupling, sequestering endothelin receptor signaling.…”
Section: Discussionmentioning
confidence: 53%
“…The endothelin system includes two GPCRs: endothelin receptor A (ET A R) and B (ET B R). Endothelin 1 (ET-1) can promote vasoconstriction by activating ET A R or promote vasodilation by activating ET B R ( 59 ). Recent studies have shown that the binding of the orphan receptor GPR75 to 20-hydroxyeicosatetraenoic acid (20-HETE) activates the Gα q/11 protein, which causes vasoconstriction ( 69 ).…”
Section: Gpcrs In Vascular Function and Diseasementioning
confidence: 99%